Mengembangkan Loyalitas Melalui Strategi Kualitas Layanan dan Kepercayaan Pada Industri Perbankan - Jumadi Jumadi; Jamal Abdul Naser; Gendut Budi Wahyono (Program Pascasarjana Universitas Gajayana, 2019)
This study attempts to know how much compensation factors have leverage a significant impact on the performance of an Account Representative through motivation to labor as variable mediation in kpp pratama singosari .This research is research quantitative with the design survey by using questionnaire. Population research used is an Account Representative excavation potential KPP pratama singosari as many as 28 respondents and all used as respondents with the methods census. This research result indicates that compensation have had a positive impact and significant on the performance with coefficient value of 0,416 and motivation have had a positive impact and significant on the performance with coefficient value of 0,215 and motivation work be variables mediate between compensation on performance.